PELATIHAN PUBLIKASI JURNAL HASIL PENELITIAN TINDAKAN KELAS BAGI GURU SLB N 1 BANTUL YOGYAKARTA - Hidayat, Luqman; Noormiyanto, Faiz (Universitas PGRI Yogyakarta, 2020)
This training gives knowledge to teachers in Special Education Needs School 1 Bantul to overcome difficulties in publishing articles on the results of classroom action research (CAR) to OJS-based journals (Open Journal System). The target to be achieved through this activity is to increase teacher competence in making / compiling articles on the results of classroom action research and providing skills in submitting OJS-based journals. Besides increasing teacher competence. Service activities carried out through several training methods, namely: 1) lecture method, 2) question and answer method, and 3) simulation method. The training was carried out 4 times in theory and practice, this was done so that the teachers not only understood the theory, but the teacher could also be independent in making articles and submit OJS journals properly. The results achieved are the teacher can compile an PTK result article and upload it to the OJS journal.